2019
DOI: 10.1080/07359683.2019.1575059
|View full text |Cite
|
Sign up to set email alerts
|

Reducing health inequalities trough digital options in mental health: A physician’s perspective

Abstract: This paper explores the physicians' perspective regarding the potential of computerised Cognitive Behavioural Therapies (cCBTs) to overcome inequalities in the context of mental health care provision. The main benefits were related to the ability of cCBTs to provide care in a convenient and efficient manner, enhancing its accessibility. These aspects were perceived more important than cost-effectivity of treatment, which is often claimed to be the key benefit of cCBTs. Age and general acceptance of CBT were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…These effects could be due to patient-group differences: patients referred from occupational health are, by definition, employed and presumably have a higher average level of functioning, higher socioeconomic status, and a lower likelihood of serious comorbidities. Moreover, in our recent study, physicians in occupational health displayed more interest in sending patients to iCBT than their primary care counterparts [62], which may transfer into patients' own expectations and motivation.…”
Section: Patients' Background Effectsmentioning
confidence: 83%
“…These effects could be due to patient-group differences: patients referred from occupational health are, by definition, employed and presumably have a higher average level of functioning, higher socioeconomic status, and a lower likelihood of serious comorbidities. Moreover, in our recent study, physicians in occupational health displayed more interest in sending patients to iCBT than their primary care counterparts [62], which may transfer into patients' own expectations and motivation.…”
Section: Patients' Background Effectsmentioning
confidence: 83%
“…Some retailers and manufacturers had made tweets empathising the sufficiency of toilet paper supplies, in hope to counterbalance the spread of anxiety and panic buying behaviours. Using digital platforms to enhance access to health services including mental health support is not a new idea, however, general uptake of digital mental health applications has been low in many countries [25]. The COVID-19 pandemic may be a good opportunity to explore the feasibility of digital health options [26].…”
Section: Discussionmentioning
confidence: 99%
“…The patient interviewees felt empowered by this tool, but it could also disempower other patient groups who have not mastered e-consultations. Indeed, research has shown that while digital solutions might reduce inequalities for some groups, for example, those with mental health issues (Taiminen et al, 2019), for other groups, digital solutions may exacerbate health inequalities (Rich et al, 2019).…”
Section: Discussionmentioning
confidence: 99%